Measurement of b hadron lifetimes in pp collisions at root s=8TeV - Sirunyan, A. M. (2018)
Measurements are presented of the lifetimes of the B-0, B-s(0), Lambda(0)(b), and B-c(+) hadrons using the decay channels B-0 -> J/psi K*(892)(0), B-0 -> J/psi K-S(0), B-s(0) -> J/psi pi(+)pi(-), B-s(0) -> J/psi phi(1020), Lambda(0)(b) -> J/psi Lambda(0), and B-c(+) -> J/psi pi(+). The data sample, corresponding to an integrated luminosity of 19.7 fb(-1), was collected by the CMS detector at the LHC in proton-proton collisions at root s = 8TeV. The B-0 life-time is measured to be 453.0 +/- 1.6 (stat) +/- 1.8 (syst) mu m in J/psi K*(892)(0) and 457.8 +/- 2.7 (stat) +/- 2.8 (syst) mu m in J/psi K-S(0), which results in a combined measurement of c tau(0) = 454.1 +/- 1.4 (stat) +/- 1.7 (syst) mu m. The effective lifetime of the B-s(0) meson is measured in two decay modes, with contributions from different amounts of the heavy and light eigenstates. This results in two different measured lifetimes: c tau(0)(Bs) -> J/psi pi(+)pi(-) = 502.7 +/- 10.2 (stat) +/- 3.4 (syst) mu m and c tau(0)(Bs) -> J/psi phi(1020) = 443.9 +/- 2.0 (stat) +/- 1.5 (syst) mu m. The Lambda(0)(b) lifetime is found to be 442.9 +/- 8.2 (stat) +/- 2.8 (syst) mu m. The precision from each of these channels is as good as or better than previous measurements. The B-c(+) lifetime, measured with respect to the B+ to reduce the systematic uncertainty, is 162.3 +/- 7.8 (stat) +/- 4.2 (syst) +/- 0.1 (tau(B+)) mu m. All results are in agreement with current world-average values.